Méthodes de recherche innovantes et alternatives en économie et gestion; Innovative and alternative research methods in economics and business administration - Anne Bartel-Radic (European Institute for Knowledge & Value Management (EIKV), 2019)
– This book brings together various contributions on research methods that can be qualified as innovative or alternative in the fields of economics and management. These are methodologies that are atypical as defined by their novelty, but even so this is quite relative; often, these methodologies are already commonly used in other disciplines, but still unknown in economics or management. They cover the entire spectrum including intrinsically qualitative methodologies such as action research and biographical analysis, quantitative methodologies such as experimentation and analysis of interval scales, as well as a methodology considered as halfway between "quali" and "quanti": the QCA method. Some of the texts were in French, others in English. Rather than translate everything into one language and "deny" some of the potential readers access to the texts, the authors chose to write a bilingual book. Thus, all the six chapters are in both French and English.
Keywords: 650